(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Mishenina T. M. The organization of work with students of philological specialties with indeclinable nouns in the Ukrainian language: problem based approach. In the article the nature of the work organization with students of philological specialties with indeclinable nouns in the Ukrainian language on the basis of a problematic approach which will promote the solution of the didactic, practical, developing and checking tasks in the process of training of future teachers of philological specialties has been explained. The system of problem tasks aimed at problem solving of modern Ukrainian Studies: lexical-semantic and grammatical mastering of indeclinable nouns at the present stage of the Ukrainian language functioning has been developed.